Development of Multiscale Models for Complex Chemical Systems: From H+H2 to Biomolecules (Nobel Lecture)1. Issue 38 (27th July 2014) - Karplus, Martin
<x xml:space="preserve">Abstract</x> Although the laws governing the motions of atoms are quantum mechanical, the key realization that made possible the simulation of the dynamics of complex systems, including biomolecules, was that a classical mechanical description of the atomic motions is adequate in most cases. From M. Karplus' own perspective, this realization was derived from calculations on the symmetric exchange reaction, H+H2→H2+H.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>